The foundations of international political virtue - Malone, C (2013)
This thesis provides the theoretical groundwork for a 'virtue ethical' account of international political conduct. The project begins by investigating the distinct patterns of normative theorising within international scholarship, noting not only that moral philosophical foundations are unpronounced and interchangeable, but that even in this diminished capacity the influence of virtue ethical thought is limited and fragmentary relative to its competitors. Redressing this underrepresentation is thus dually motivated: developing a fresh perspective on important global issues, whilst also subjecting the theory to an atypical angle of scrutiny. Adapting virtue ethics to the international realm requires, most essentially, that we settle the level at which its concepts should be applied. Can the theory’s central focus on character be reconciled with the collective nature of global political interaction? Can we accurately ascribe virtues and vices to governments and states? These questions of group agency form the heart of thesis investigation. Beginning from abstract foundations, the possible justification for such ascriptions is sought in competing theories of joint action and attitude. The 'individualist' accounts of Searle and Bratman are ultimately rejected in favour of Gilbert's non-reductive 'plural subject' theory, and - presenting group-level accounts of intention, motivation, practical wisdom, emotion and disposition around her concept of 'joint commitment' - a general model of collective character is constructed. Allied to additional requirements of moral responsibility, this framework is then used to assess the virtue-capability of actual political bodies, considering the decision-making hierarchy of the United Kingdom as a case study for the modern state. Tracing the route of policy authorisation across cabinet, government and parliament, a sophisticated yet ultimately impermanent picture of group-virtue-ethical agency is established, in tension with the notion of enduring state liability. By shifting focus to the national level, it is argued that this fluctuating footprint of agency can nevertheless be unified, modifying Gilbert’s notion of a 'population joint commitment' to tie institutional virtue and vice to a persisting state identity. This provides a template for international character evaluation.